Swiss Democracy Possible Solutions to Conflict in Multicultural Societies - Linder, Wolf; Mueller, Sean (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This open access book provides an updated and fully revised 4th edition of this authoritative analysis of Swiss democracy. It particularly explains the institutions of federalism and consensus government through political power sharing. In this new edition, the authors also address several important changes and challenges that have affected Swiss democracy, including the country's relationship with the EU, fiscal equalisation, direct democracy and the legitimacy of national referendums, territorial conflict, as well as the polarisation of party politics. Wolf Linder is Professor emeritus of the Institute of Political Science, University of Berne, Switzerland. His main areas of research are Swiss politics, direct democracy and Europeanisation. Sean Mueller is Senior Researcher at the Institute of Political Science, University of Berne, Switzerland. His main areas of research are Swiss and comparative federalism, power-sharing and direct democracy. .